A European banking business models analysis: the investment services case. Issue 1 (12th February 2018) - Musile Tanzi, Paola; Aruanno, Elena; Suardi, Mattia
Abstract : Purpose: Business Model Analysis is acquiring increasing visibility in the European banking regulatory framework, following the European Banking Authority guidelines on common procedures and methodologies for the supervisory review and evaluation process (SREP), developed to assess business and strategic risks (EBA, 2014, 2015a, 2015b, 2015c ). Starting from a selected literature review, in the paper, the authors analyse business models set up by financial intermediaries, bank and non-banks, for the distribution of investment services, first by comparing European niche players with European banking global players, and second, comparing European niche players among themselves to understand the evolution of business models for the distribution of investment services at European level. The research is supported by the Baffi–Carefin Research Centre at the Bocconi University (Italy), in collaboration with ANASF, the Italian Association of Financial Advisors (Italy). Design/methodology/approach: The authors consider a sample of European financial players from 2009 to 2014. The authors' focus is on France, Germany, Italy, The Netherlands, Spain and the UK; overall the authors' handmade data set is based on 162 annual reports. The authors follow two main questions: Do the niche players, as they are focused on the distribution of investment services, have an upper limit to profitability, compared to the global players, as risk-takers in many financial areas? How is the business model of niche players changing, facing increasing competition and regulatory pressures? Findings: Answering the first research question, the highest net profitability is found in the niche players group; the global players, as risk-takers, achieve lower remuneration, in contrast with the risk premium theory. The results were assessed over a limited period, however, deemed in line with the company's strategic planning horizon. Answering the second research question, the authors focus on the case of niche players, using a cluster analysis. The authors identify three different business models: most dynamic niche players, which combine investment services, insurance and welfare services, achieving the highest margins and stability; players mainly focused on asset management, whose key vulnerability is the degree of open architecture, especially in light of future MiFID 2 implementation; and players mainly focused on the creation of well-structured on-line platforms, which offer also brokerage services, thereby reducing their marginality and potentially increasing their business risk. Research limitations/implications: Despite the limited time series, the authors' research gives some inputs for those interested in deepening the business model analysis focus on the distribution of investment services and the business and strategic risk assessment, both for the global banks and the niche players (banks and non-banks). Practical implications: The authors' results could be of some interest during the strategic assessment of global banks and niche players, both adopting an internal perspective or an external one, as regulator. Social implications: By giving some specific insights into the assessment and comparison of business and strategic risks among global and niche players, the authors' research provides the basis for further research in the field of the distribution of investment services. Originality/value: The originality mainly regards the business model risk perspective and the focus of the authors' analysis: the distribution of investment services. This sector, unlike the asset management, does not have an easily recognisable group of comparables at European level, all the European countries analysed have very different business models. This research avails of an original database, that is unique to Europe.